2015
DOI: 10.1371/journal.pone.0135064
|View full text |Cite
|
Sign up to set email alerts
|

Down but Not Out: The Role of MicroRNAs in Hibernating Bats

Abstract: MicroRNAs (miRNAs) regulate many physiological processes through post-transcriptional control of gene expression and are a major part of the small noncoding RNAs (snRNA). As hibernators can survive at low body temperatures (Tb) for many months without suffering tissue damage, understanding the mechanisms that enable them to do so are of medical interest. Because the brain integrates peripheral physiology and white adipose tissue (WAT) is the primary energy source during hibernation, we hypothesized that both o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 68 publications
0
18
1
Order By: Relevance
“…2b). Tissue-specific miRNA expression has been reported during hibernation in thirteen-lined ground squirrels [33][34][35], little brown bats (Myotis lucifugus) [36][37][38], monito del monte (Dromiciops gliroides) [6], and wood frog (Rana sylvatica) [39] (Fig. 5).…”
Section: Control Of Gene Expressionmentioning
confidence: 99%
“…2b). Tissue-specific miRNA expression has been reported during hibernation in thirteen-lined ground squirrels [33][34][35], little brown bats (Myotis lucifugus) [36][37][38], monito del monte (Dromiciops gliroides) [6], and wood frog (Rana sylvatica) [39] (Fig. 5).…”
Section: Control Of Gene Expressionmentioning
confidence: 99%
“…A growing number of studies by our lab, and others, have demonstrated the essential role of miRNA differential expression in modulating global gene suppression and coordinating the up-regulation of selected genes in response to torpor, estivation, anaerobiosis, and freezing 27 33 34 35 36 37 38 39 40 41 . To our knowledge, the present study is the first to investigate miRNA expression in relation to torpor in a marsupial species.…”
mentioning
confidence: 99%
“…Differential expression of ncRNAs in animal models of cold adaptation has garnered significant interest in the field over recent years. Modulation in expression of ncRNAs, in particular miRNAs, at low temperatures has been reported in small mammalian hibernators [22] , [23] , cold-hardy insects [24] , and freeze-tolerant wood frogs [25] . Unlike miRNAs, lncRNAs have not been explored extensively in models of cold adaptation.…”
Section: Discussionmentioning
confidence: 97%